The Circular Economy in the Popular Republic of China: A Multilevel Strategy for a New Model of Economic and Social Development - Senatore, Gianluca (Mediterranean Journal of Social Sciences, 2021)
The following work analyzes the principal differences in the implementation of the circular economy model between Europe and China, with a focus on practices and strategies set in place by the asiatic Popular Republic to promote the sustainable development. For that purpose, in this work, relevant trial studies on the management and deployment of circular economy in China and on green behaviors of Chinese population have been examined Â  Received: 20 July 2021 / Accepted: 30 August 2021 / Published: 5 September 2021